Photo-responsive pseudorotaxanes and assemblies. (1st December 2014) - Mandal, Amal Kumar; Gangopadhyay, Monalisa; Das, Amitava
Abstract : Optical responses for understanding the dynamic conformational change(s) in solution during the stimuli responsive complexation and decomplexation process(es) in a supramolecular assembly. Abstract : Chemists have achieved a predictable control over various non-covalent interactions and have used these weak interactions in their favour for developing a plethora of intricate functional structures. In this tutorial review we have summarized reports on such supramolecular structures that describe the rational approach in designing host and/or guest components, tagged with an appropriate fluorophore, for achieving the modified optical responses on formation of an assembly. This has relevance for designing new photo-responsive smart or adaptive stimuli responsive functional materials, self-healable materials, with interesting photo-physical property. These are also important in the area of supramolecular chemistry and biophysical chemistry in predicting the relative conformation in solution.